The generation of oligodendroglial cells is preserved in the rostral migratory stream during aging - Capilla-Gonzalez, Vivian; Cebrian-Silla, Arantxa; Guerrero-Cazares, Hugo; Garcia-Verdugo, Jose Manuel; Quinones-Hinojosa, Alfredo (Frontiers in Cellular Neuroscience, 2013)
The subventricular zone (SVZ) is the largest source of newly generated cells in the adult mammalian brain. SVZ-derived neuroblasts migrate via the rostral migratory stream (RMS) to the olfactory bulb (OB), where they differentiate into mature neurons. Additionally, a small proportion of SVZ-derived cells contribute to the generation of myelinating oligodendrocytes. The production of new cells in the SVZ decreases during aging, affecting the incorporation of new neurons into the OB. However, the age-related changes that occur across the RMS are not fully understood. In this study we evaluate how aging affects the cellular organization of migrating neuroblast chains, the proliferation, and the fate of the newly generated cells in the SVZ-OB system. By using electron microscopy and immunostaining, we found that the RMS path becomes discontinuous and its cytoarchitecture is disorganized in aged mice (24-month-old mice). Subsequently, OB neurogenesis was impaired in the aged brain while the production of oligodendrocytes was not compromised. These findings provide new insight into oligodendrocyte preservation throughout life. Further exploration of this matter could help the development of new strategies to prevent neurological disorders associated with senescence.